(untitled) (Progressive Agriculture, 2013)
Zebra is the member of the equide family available at Dhaka Zoo and gradually disappeared due to inadequate health management and varies maladies. The aim of this study was to investigate the cause of illness and death of zebras (Equus burchelli) at Dhaka Zoo. Two zebras died on 10 and 25 January, 2010, one become seriously ill on 15 February, 2010 and was considered as the study samples. The dead animals were necropsized, representative samples were collected in formalin for histopathological examination. Thoracic fluid, cardiacfluid, abdominal fluid and blood from these zebras were also used for isolation of causal bacteria. Blood sample was also collected from the sick zebra and subjected for bacteriological examination. Results of necropsy examination revealed hydrothorax, pneumonia and septicemia. Histopathological findings revealed pulmonary emphysema, interstitial pneumonia, bronchitis, pulmonary thrombosis, exudates in lung alveoli and granulomatous lesions in lungs. Other important findings were hemosiderosis and anthracosis. Based on the cultural, morphological and biochemical tests, Pasteurella sp. was identified. Bacteriological examination revealed that the organism bears similarities with P. multocia, P. hemolytica and P. aerogenes but definite bacterial species was not identified. The zebras were collected from Africa and the bacterial nature identified was Pasteurella but definite species could not be identified; could be a Pasteurella available in Africa. Therefore, it needs investigation at other biochemical and genetic level to confirm the bacterial species involved. There occurrence of similar disease at later on was also observed in zebra at DhakaZoo and responded well to treatment for pasteurellosis; the cause of illness was, therefore, confirmed as Pasteurellosis. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16755 Progress. Agric. 21(1 & 2): 83 - 92, 2010